Cardiovascular, cancer and mortality events after bariatric surgery in people with and without pre‐existing diabetes: A nationwide study. Issue 4 (7th October 2018) - Dhalwani, Nafeesa N.; Zaccardi, Francesco; Waheed, Hina; Mytton, Jemma; Papamargaritis, Dimitris; Webb, David R.; Evison, Felicity; Lilford, Richard; Davies, Melanie J.; Khunti, Kamlesh
Abstract : Highlights Patients with diabetes carry a residual risk of cardiovascular, cancer, and mortality events after bariatric surgery: compared with patients without diabetes, the risk is 26%, 21%, 42%, and 61% higher for all‐cause mortality, cancer, heart failure, and stroke, respectively, and double for myocardial infarction. The risk of death after bariatric surgery remains higher in patients without diabetes than in subjects of same age from the general population. Abstract: Background: Bariatric surgery reduces cardiovascular events and mortality risk in obese individuals. However, it is unclear whether diabetes modifies this effect. This study examined mortality, cardiovascular, and cancer risk following bariatric surgery in adults with and without pre‐existing diabetes. Methods: Using mortality‐linked Hospital Episodes Statistics (2006‐14) from England, the risk of death, myocardial infarction, stroke, unstable angina, heart failure, and cancer following bariatric surgery was examined; the risk of death in people undergoing surgery was also compared with mortality rates of the general population. Results: Of the 35 887 people undergoing bariatric surgery, 9175 (25.6%) had pre‐existing diabetes. During a mean follow‐up of 5.3 years, 801 people died, of whom 293 (36.6%) had pre‐existing diabetes. The risk of all‐cause mortality was 26% higher in people with than without diabetes (adjusted hazard ratio [aHR] 1.26, 95% confidence interval [CI] 1.08‐1.46), whereas the risk of cancer was 21% higher (aHR 1.21; 95% CI 1.14‐1.77). The risk of cardiovascular events was higher for patients with than without diabetes (aHRs [95% CIs] 2.08 [1.42‐3.05], 1.80 [1.29‐2.52], 1.61 [1.18‐2.19], and 1.42 [1.14‐1.77] for myocardial infarction, unstable angina, stroke, and heart failure, respectively). Compared with the general population, the age‐standardized mortality rate ratio was 1.70 (1.52‐1.91) and 1.35 (1.23‐1.48) in people with and without pre‐existing diabetes, respectively. Conclusions: For patients with pre‐existing diabetes, the risk of death, cardiovascular events, and cancer after bariatric surgery was higher than for those without diabetes, whose mortality risk after surgery remains 35% higher than that of the general population.